Răspunsuri

Cel mai inteligent răspuns!
2014-08-14T20:33:01+03:00
(x - 4)(y + 3) = 35

Avem solutiile:

S1:   35 = 1 * 35 => x - 4 = 1 si y + 3 = 35  => x = 5  si  y = 32
S2:   35 = 5 * 7   => x - 4 = 5 si y + 3 = 7   => x = 9  si  y = 4
S3:   35 = 7 * 5   => x - 4 = 7 si y + 3 = 5   => x = 11 si y = 2
S4:   35 = 35 * 1 => x - 4 = 35 si y + 3 = 1  => x = 39 si y = -2

 S5:   35 = -1 * (-35) => x - 4 = -1 si y + 3 = -35  => x = 3   si  y = -38
S6:   35 = -5 * (-7)   => x - 4 = -5 si y + 3 = -7   => x = -1   si  y = -10
S7:   35 = -7 * (-5)   => x - 4 = -7 si y + 3 = -5   => x = -3   si y = -8
S8:   35 = -35 * (-1) => x - 4 = -35 si y + 3 = -1  => x = -31 si y = -4

unde S1, S2, ...... S8  sunt Solutia 1, Solutia 2, ...... Solutia 8



1 5 1